Implementation of the Complete Systematic Land Registration Policy (PTSL) in Tempuran District, Lemah Duhur Village - Aripin, Rizal; Dewi, Sartika; Yani, Abdul; Rahmadhani, Defirstta; Ramdhani, Muhamad Sadam; Gunawan, Rizka Putri; Santosa, Sandiya Adi (PT. Hafasy Dwi Nawasena, 2024)
The implementation of the Complete Systematic Land Registration (PTSL) policy often faces various challenges or problems. Therefore, the National Land Agency (BPN) has the responsibility to overcome these problems. This research uses a qualitative research method with an empirical juridical approach. The purpose of this research is to find out how the implementation of the Complete Systematic Land Registration (PTSL) policy in Lemah Duhur Village, Tempuran District, Karawang Regency, and the obstacles that hinder its implementation. The research findings show that the implementation of the PTSL policy in Lemah Duhur Village has gone well but faces several challenges. Data from the National Land Agency (BPN) shows that of the 1,800 land parcels targeted in 2017, many have yet to be surveyed, indicating a gap between targets and results. Challenges include suboptimal socialization efforts, a lack of competence among adjudication committees, and the issue of inaccurate land measurement and mapping compared to the certificate layout.